The effect of social appearance anxiety and body perception on the quality of life in burn patients - Yesilyurt, Ilayda; Kendirkiran, Gulcan (Wiley, 2024)
This study was conducted with a descriptive and cross-sectional design to demonstrate the effect of social appearance anxiety and body perception on quality of life in burn patients. The study was conducted in the intensive care units and burn clinic of Elazig Firat University Hospital between 17 February 2022 and 30 April 2022. Data were collected from 94 burn patients using the Personal Information Form, Social Appearance Anxiety Scale, Body-Cathexis Scale and Quality of Life Scale-Short Form. Most participants were 30 years old and under, male, married, had no children and had an education level of high school or below. Most had social security and an income equal to their expenses. They were not uncomfortable with coming to the hospital, and 1-3 months had passed since the burn incident. They did not spend time outside, and most had no part of their bodies that they did not like, while 26.1% did not like their feet. A negative relationship was detected between the Social Appearance Anxiety Scale and Body-Cathexis Scale, and a positive relationship between the total and sub-dimensions of the Quality of Life Scale (p > 0.05). There was a negative relationship between the Body-Cathexis Scale and the Quality of Life Scale total and sub-dimensions (p < 0.05), and a positive relationship between the total and sub-dimensions of the Quality of Life Scale (p < 0.05).
Keywords: anxiety; burns; physical appearance; quality of life; social perception